APPLICATION INTEGRATION METHODS ON LANDSAT ETM + TO DETERMINE EARTHQUAKE POTENTIALS IN PALU GRABEN - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
This study aims to assess the ability of the integration method at Landsat ETM + imagery in recognizing objectfault, mainfault and secondaryfault in Palu Graben. Mapping offault and calculate earthquakepotential, based offault that is found in Graben of Palu. The image used in this study is Landsat ETM +. Techniques used to process Landsat ETM + is a method of integration. Landsat ETM+ imagery processed with ENVI software 4.4, while the mapping offaults and determining of length using ArcGIS 9.2.The potential of earthquakes is calculated from the length offaults found in the Graben of Palu. Results obtained showed that the patterns of lineament as a picture of fault in the Palu Graben can be extracted from Landsat ETM +. Lineament offault is seen clearly on Landsat ETM + image processed with integration method and band combination, 45PC1_8. Faults are arranged in the form of map. There are 66 faults found at research sites. Magnitude earthquake 5,5 SR can beproduced from thefault with a length greater than or equal to 9 km. If each faults contributes the same to earthquake occurrence, the potential incidence of earthquake with magnitude greater than or equal to 5.5 SR in the Graben of Palu is 33.8%, while the magnitude is smaller than 5.5 SR is 66.2%. The ~argestmagnitude that can.occur in Palu Graben, 7.1 SR. These results indicate that the potential earthquake "destructive~ 5.5 SR) of approximately 33.8%